Analysis of the Influence of Service Quality, Emotional Satisfaction and Company Image on Customer Loyalty of Indihome PT Telkom Indonesia (Persero) Tbk - Isvari Hidayati; Nuril Huda (International Journal of Business and Applied Economics, 2023)
This study aims to analyze the influence of quality service (X1), emotional satisfaction (X2), and image of the company (X3) as variables free and loyal customers (Y) as variables bound. Data collection techniques include a questionnaire with a sample of as many as 145 people. The data analysis technique used To determine the influence between variables in the study is PLS-SEM. Research results show that Quality of Service influences customers' Emotional Satisfaction. Quality of Service and Emotional Satisfaction influence Corporate Image. Corporate Image influences Customer Loyalty. Quality of Service and Emotional Satisfaction have no influence on Customer Loyalty to Indihome at Plasa Telkom Banjarmasin.